KONSEP KEJAHATAN DALAM AL-QURAN (Perspektif Tafsir Maudhuâi) - Muhammadun, Muzdalifah (DIKTUM: Jurnal Syariah dan Hukum, 2011)
This article describes the concept of evil in the Quran with commentary maudhui approach. The results of this study obtained information that the Quran uses several terms to represent various forms of crimes committed by humans. Among these terms are al-fasad, al-fusuq, al-isyan, al-itsm, al-zulm, al-fahsiyah, al-munkar, al-bagy, al-batil dan makr. Based on the etymological sense contained in the word and by looking at the context of its use in the Quran, it is understood that: 1) Ontology crime is the use of one of the potential given by Allah SWT. outside the corridor he has set, 2) Existence of evil in the Quran include crimes against God, a crime against the environment, the social evil, evil cultural, economic crimes, crimes of personal and communal, 3) factors causing crime is an internal factor in the form of insularity and ignorance, arrogance and hubris, despair in life. In addition to external factors ie Satans temptation and pleasure. As a result of the crime is the appearance of damage (al-facade) and evil (al-syarr).